The impact of surgical intervention on renal function in cystinuria - Döven,Serra Sürmeli (2018)
ABSTRACT Introduction: Cystinuria is an autosomal recessive disorder due to intestinal and renal transport defects in cystine and dibasic amino acids, which result in recurrent urolithiasis and surgical interventions. This study aimed to assess the impact of surgical interventions on renal function by analyzing estimated glomerular filtration rates. Methods: Thirteen pediatric patients with cystinuria, who were followed-up in a single tertiary institution between 2004 and 2016, were included in the study. Medical records were reviewed to collect data on clinical presentation of patients, urine parameters, stone formation, medical treatment, surgical intervention, stone recurrence after surgical procedure, stone analysis, ultrasonography, 99m-technetium dimercaptosuccinic acid (99mTc-DMSA) radionuclide imaging results, and follow-up time. Creatinine clearances estimated by modified Schwartz (eGFR) formula before and after surgery were used to assess renal function and compared statistically. Results: Nine patients (69.2%) had renal scarring which were detected with 99mTc-DMSA radionuclide imaging. In ten patients (76.9%), open surgical intervention for stones were needed during follow-up. Significant difference was not detected between eGFR before and after surgical intervention (mean 92 versus 106, p = 0.36). Nine of the patients (69.2%) were stone free in the last ultrasonographic examination. Relapses of stone after surgery were seen in 66.6% of patients who underwent surgical intervention. Conclusions: Surgical interventions for urinary stones are commonly required in patients with cystinuria. Renal scarring is a prevalent finding in cystinuric patients. Surgical interventions have no negative impact on eGFR in patients with cystinuria according to the present study.